Current developments and future directions in COPD. (2nd December 2020) - Mathioudakis, Alexander G.; Vanfleteren, Lowie E.G.W.; Lahousse, Lies; Higham, Andrew; Allinson, James P.; Gotera, Carolina; Visca, Dina; Singh, Dave; Spanevello, Antonio
The European Respiratory Society journals publish respiratory research and policy documents of the highest quality, offering a platform for the exchange and promotion of scientific knowledge. In this article, focusing on COPD, the third leading cause of death globally, we summarise novel research highlights focusing on the disease's underlying mechanisms, epidemiology and management, with the aim to inform and inspire respiratory clinicians and researchers. Current developments and future directions in COPD: a critical summary of some of the most recent ground-breaking research studies and policy documents from @ERSpublications https://bit.ly/3oW0xDM